Challenges of Integrating Green Skills in the Indonesian Vocational Training System - Eddy Sabarudin (Green Publisher Indonesia, 2026)
The transition toward a green economy necessitates a workforce equipped with green skills as a core competency to support industrial sustainability and competitiveness. However, the integration of green skills into the vocational training system in Indonesia continues to face various structural challenges and has yet to be managed in a systematic manner. This study aims to analyze the concept of green skills through the lens of the most recent literature, identify the challenges of their integration within vocational training institutions, and examine early practices of green skills implementation through a case study at the LPP Quantum Sampit Vocational Training Institute (Lembaga Pelatihan Profesi Quantum Sampit). The research employed an integrative literature review combined with an explanatory case study approach, utilizing policy document analysis, international reports, and graduate tracer data from LPP Quantum Sampit for the period 2022–2025. The findings reveal six principal challenges in the integration of green skills: limitations in the existing policy framework; a curriculum that is not yet oriented toward green principles; insufficient instructor competence; inadequate training facilities and equipment; increasingly complex industry demands; and the absence of established green skills certification standards. These findings serve as the basis for the formulation of conceptual recommendations in the form of a five-pillar green skills integration framework, proposed as a strategic effort to strengthen the vocational training system in supporting Indonesia's transition to a green economy.